In the eye of the sun - Soueif, Ahdaf (Anchor Books, 2000)
Set amidst the turmoil of contemporary Middle Eastern politics, this vivid and highly-acclaimed novel by an Egyptian journalist is an intimate look into the lives of Arab women today. Here, a woman who grows up among the Egyptian elite, marries a Westernized husband, and, while pursuing graduate study, becomes embroiled in a love affair with an uncouth Englishman.